2023
DOI: 10.1126/sciadv.add0324
|View full text |Cite
|
Sign up to set email alerts
|

A molecular framework for grain number determination in barley

Abstract: Flowering plants with indeterminate inflorescences often produce more floral structures than they require. We found that floral primordia initiations in barley ( Hordeum vulgare L.) are molecularly decoupled from their maturation into grains. While initiation is dominated by flowering-time genes, floral growth is specified by light signaling, chloroplast, and vascular developmental programs orchestrated by barley CCT MOTIF FAMILY 4 ( HvCMF4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 83 publications
2
16
0
Order By: Relevance
“…While GT1 and VRS1 homologs may regulate the number of flowers that develop, additional genetic components may contribute to the maturation of those flowers into seeds. In barley, the CCT MOTIF FAMILY4 (CMF4) gene modulates spikelet survival and maturation through the vascular-associated circadian clock and organ greening (Huang et al, 2023). To maximize the yield-related effect of developing or selecting GT1 and VRS1 homolog alleles that permit more floral development, concurrent selection of floral ←Figure 3: The growth repression role of VRS1 and GT1 homologs is conserved in brachypodium.…”
Section: Discussionmentioning
confidence: 99%
“…While GT1 and VRS1 homologs may regulate the number of flowers that develop, additional genetic components may contribute to the maturation of those flowers into seeds. In barley, the CCT MOTIF FAMILY4 (CMF4) gene modulates spikelet survival and maturation through the vascular-associated circadian clock and organ greening (Huang et al, 2023). To maximize the yield-related effect of developing or selecting GT1 and VRS1 homolog alleles that permit more floral development, concurrent selection of floral ←Figure 3: The growth repression role of VRS1 and GT1 homologs is conserved in brachypodium.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that meiotic ability or anther greening at pre‐dimorphism phase was a critical indicator or threshold between fertile or abortive potential of floret primordia. There was an association between anther greening and the ability to become a fertile floret (Huang et al, 2023; Zhang et al, 2021). It is unclear whether the meiotic ability or anther greening was the cause or consequence of floret primordia abortion.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether the meiotic ability or anther greening was the cause or consequence of floret primordia abortion. Previous research revealed that anther greening was dependent on vascular signals and chloroplasts development in the anther (Huang et al, 2023). We rather thought that those floret primordia without meiotic ability or anther greening at pre‐dimorphism phase still did have the capacity to become green and perform meiosis but they were developmentally arrested or inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce background introgressions from the original mutagenesis recipient (cv. Donaria), we further backcrossed BW883 to wild-type Bowman plants ( Huang et al , 2023 ). The isogenic six-rowed GP -vrs1 line was obtained through targeted mutagenesis conducted by CRISPR-associated (Cas) endonuclease technology ( Thirulogachandar et al , 2024 ).…”
Section: Methodsmentioning
confidence: 99%
“…The influence of spikelet fertility on rachis vasculature was studied in an isogenic six-rowed GP -vrs1 line generated by targeted mutagenesis ( Thirulogachandar et al , 2024 ), and for the effect of a reduction in fertile spikelets, we compared the cv. Bowman with its near-isogenic mutant BW -tst2.b ( Huang et al , 2023 ) exhibiting extended pre-anthesis tip degeneration. Our results confirm the assumption of Waddington et al (1983) that the morphogenesis of the barley rachis vasculature is the result of two distinct processes: initiation and processing, with ultimate vein size being strongly correlated with the number of fertile spikelets.…”
Section: Introductionmentioning
confidence: 99%